The poetry attributed to The Islamic orthodox caliphs (Journal of the College of Education for Women, 2019)
The Islamic orthodox caliphs had a great importance in the history of Arabs inparticular, and of Muslims in general.Some attributed poetry to them. This issue to see whether such an attribution is corrector not.This research tried to deal objectively with this poetry .it discussed the topic,exploring the scholars’ opinions about poetry attributed to the Islamic orthodoxCaliphs, stating their dispute : some of them agreed while others rejected theattribution.The research adopted the opinon that had rejected for reasons stated in theresearch, of them: the weakness of poetry and its dealing with unimportant things, forexample, the caliph Omar composed verses about a new garment worn by him.Is it reasonable that wearing a new garment made him compose poetry, whilehis youth or the pagans who hurt the Prophet Mohammed in Mecca and Medina or theProphets death did make Omar compose poetry?When it was clarified that Omar and Ottman had not poetry, I studied thepoetical texts ascribed to Abu Bakir and Ali with an internal study. The study deniedwhat they had said as poetry, then I studied the events of reality to negate that theIslamic orthodox caliphs were poets and that is not a stain in their lives because versecomposing does not add anything to them and non-verse composing does not abatetheir high place for God and people.